Kinematic model analysis of a parallel manipulator with six and three degrees of freedom - Dejan Jovčevski; Marjan Dzidrov; Hristijan Mickoski (My University, 2019)
Model analysis of mechanism with parallel structurewith revolute kinematic pairs by six and three degrees of freedom is presented. An analytical method for solving the direct kinematics is analyzed by using analytic equations of the plane in which the movable platform of the manipulator is placed. The obtained solutions cannot be physically realized from a constructive aspect, therefore a method is proposed by simulation modellingin Matlab/Simulink andSolidWorkswhere certain constrains can be made. Respectively,this applesto the angles of rotation of kinematic revolute pairs and changes in certain dimensions, specifically the kinematics and also following the operation functionalities of the manipulator in 3D workspace.Additionally, as well through conducted PID control, the related difficulties in the analytical solution of nonlinear equations can be overcome.
Keywords: manipulator;parallel structure;direct kinematics;mechanism;platform parallel structure